Polygeline: a comprehensive review of its role as a plasma volume expander in clinical practice - Shah, Sanjay; Reddy, Rama K.; S., Vijayanand (International Journal of Research in Medical Sciences, 2025)
Plasma volume expanders (PVEs) play a crucial role in emergency situations, such as trauma, shock, and major surgery, where rapid restoration of blood volume is essential. The choice between crystalloids and colloids as PVEs depends on various factors, including their pharmacokinetic properties. This review focuses on Polygeline, a synthetic colloid, and aims to discuss its development, physico-chemical properties, pharmacokinetics, clinical efficacy in different scenarios, safety profile, and its place in therapy. The development of polygeline dates to World War I, and its composition involves urea-linked gelatin, sodium chloride, and potassium chloride. The physico-chemical properties of polygeline, such as its average molecular weight, osmolality, and colloidal oncotic pressure, contribute to its unique characteristics, including prolonged intravascular presence and isotonicity with plasma. Compared to crystalloids like normal saline and Ringer’s Lactate (RL), polygeline demonstrates a longer duration of action and higher maximum volume expansion, making it a valuable option in various clinical scenarios. The literature review includes studies on polygeline’s clinical efficacy in critically ill patients, trauma cases, intra-operative use, haemodialysis, and large-volume paracentesis. Notable findings include its effectiveness in improving hemodynamic stability, especially in trauma patients, and its safe use in haemodialysis to lower catheter-related complications. The safety profile of polygeline appears favourable, with low incidences of anaphylactoid reactions and its safe administration in critically ill patients. In comparison to hydroxyethyl starch (HES), another synthetic colloid, Polygeline seems to have advantages in terms of safety, especially in patients with renal or hepatic impairment.